Integrated Approach for Management of Root Disease Complex in Mulberry (Morus spp.) (Indian Journal of Nematology, 2024)
To develop an effective Integrated Disease Management (IDM) strategy against root disease complex involving rootknot nematode and fungi in Mulberry, a field experiment was conducted in sick soil in RBD with 7 treatments using Furadan (carbofuran 3G), Bioconsortium seperately and in combination. Results revealed that the maximum improvement in plant growth and reduction in nematode-fungal infections parameters was observed in T-6 [Furadan + Bio-consortium + niger oil cake) followed by T-4 (Bio-consortium + niger oil cake] without any significant difference between them, which improved the plant growth parameters ranging from 77.7-87.7 % and 93.8 % plant survival over the control. Nematode-fungal infection parameters were reduced to an extent of 88.0-93.0 %, by keeping the population of nematode and pathogenic fungi extremely below the economic threshold levels (ETL) in the soil. The rest of the treatments were not found significantly superior over T-6 and T-4 and were unable to improve the plant growth parameters or reduce disease severity as desired. Hence, T-4 was found an eco-friendly IDM strategy for management of root disease complex in mulberry besides preventing leaf yield loss.